Rhodococcus equi: Another great masquerader. (2021) - Shah, P.; Rojas-Moreno, C.; Alexander, J.; Vasudevan, A.; Nguyen, V.
Abstract: Rhodococcosis is a serious infection specially affecting immunocompromised populations. We report a case of disseminated infection by Rhodococcus equi in a renal transplant patient, that was initially diagnosed as histoplasmosis, highlighting the potential for confusion between rhodococcosis and other infections. Clinicians and pathologists should correlate histopathology findings with the clinical and microbiological data.